1992
DOI: 10.1111/j.1600-0684.1992.tb00575.x
|View full text |Cite
|
Sign up to set email alerts
|

A formalin inactivated whole SIVmac vaccine in Ribi adjuvant protects against homologous and heterologous SIV challenge

Abstract: Eight monkeys were immunized at 0, 4, 9, and 18 weeks with a total of 2 mg of formalin inactivated SIVmac vaccine with Ribi adjuvant. Two weeks after the last booster four immunized monkeys and two controls were challenged with 10 MID50 of live homologous virus SIVmac, and the remaining four vaccinated animals along with two controls were challenged with the heterologous SIVsm strain. All eight vaccinated monkeys resisted the virus challenge, whereas all controls became infected. Three months after the first c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…These results were confirmed and extended by Murphey-Corb et al (1989) who showed that most animals immunized with formalin-inactivated vims were protected against infection with SIV. Similar results were subsequently obtained by several laboratories using virus-infected cells (Stott et al, 1990) or partially purified virus, inactivated by aldehydes (Putkonen et al, 1991(Putkonen et al, , 1992Johnson et al, 1992a;Le Grand et al, 1992), 0-propiolactone (Stott et al, 1990), detergent (Osterhaus et al, 1992) or psoralin and UV light (Carlson et al, 1990). Several different isolates of SIV or infectious molecular clones derived from them were used to prepare the vaccine and challenge viruses.…”
Section: Inactivated Virus Vaccinessupporting
confidence: 68%
“…These results were confirmed and extended by Murphey-Corb et al (1989) who showed that most animals immunized with formalin-inactivated vims were protected against infection with SIV. Similar results were subsequently obtained by several laboratories using virus-infected cells (Stott et al, 1990) or partially purified virus, inactivated by aldehydes (Putkonen et al, 1991(Putkonen et al, , 1992Johnson et al, 1992a;Le Grand et al, 1992), 0-propiolactone (Stott et al, 1990), detergent (Osterhaus et al, 1992) or psoralin and UV light (Carlson et al, 1990). Several different isolates of SIV or infectious molecular clones derived from them were used to prepare the vaccine and challenge viruses.…”
Section: Inactivated Virus Vaccinessupporting
confidence: 68%